2009
DOI: 10.1128/aac.01032-09
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Ribosomal Protein L3 Are Associated with Oxazolidinone Resistance in Staphylococci of Clinical Origin

Abstract: Following recent reports of ribosomal protein L3 mutations in laboratory-derived linezolid-resistant (LZD r ) Staphylococcus aureus, we investigated whether similar mutations were present in LZD r staphylococci of clinical origin. Sequence analysis of a variety of LZD r isolates revealed two L3 mutations, ⌬Ser145 (S. aureus NRS127) and Ala157Arg (Staphylococcus epidermidis 1653059), both occurring proximal to the oxazolidinone binding site in the peptidyl transferase center. The oxazolidinone torezolid maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 27 publications
3
76
0
10
Order By: Relevance
“…The results suggest that TR-701 would exhibit an efficacy similar to the efficacy of lin- ezolid for S. aureus pneumonia. An unanswered question in the current study is whether TR-701 would be expected to have the same efficacy for a linezolid-resistant isolate, as has been suggested by in vitro results (32,33,46,49). The results suggest further study of TR-701 in clinical trials of pneumonia due to S. aureus is warranted and may be especially useful given the increased burden of MSSA and MRSA pneumonia in the health care setting.…”
Section: Discussionmentioning
confidence: 84%
“…The results suggest that TR-701 would exhibit an efficacy similar to the efficacy of lin- ezolid for S. aureus pneumonia. An unanswered question in the current study is whether TR-701 would be expected to have the same efficacy for a linezolid-resistant isolate, as has been suggested by in vitro results (32,33,46,49). The results suggest further study of TR-701 in clinical trials of pneumonia due to S. aureus is warranted and may be especially useful given the increased burden of MSSA and MRSA pneumonia in the health care setting.…”
Section: Discussionmentioning
confidence: 84%
“…Mutations in these proteins have only recently been described, and their association with resistance is less certain than that of mutations found in the 23S rRNA gene. Initially, in vitro studies suggested that these mutations conferred reduced susceptibility to linezolid (20). Since that time, though, few studies have confirmed the association between these mutations and linezolid resistance, making this only a minor limitation of our study.…”
Section: Discussionmentioning
confidence: 87%
“…The L3 Leu101Val substitution was previously detected in a linezolid-susceptible clinical isolate (data on file, JMI Laboratories). However, Gly155 and Ala157 were previously implicated in disturbing linezolid binding (8,9). Thus, due to the proximity of these amino acid substitutions to those found in this study, the L3 mutations coupled with cfr may act synergistically and possibly contribute to the elevated linezolid MIC results.…”
mentioning
confidence: 70%